Sleep Changes in Adolescents Following Procedural Task Training - Nader, Rebecca S.; Murkar, Anthony L.; Smith, Carlyle T. (Frontiers in Psychology, 2016)
Recent research has suggested that some of the inter-individual variation in sleep spindle activity is due to innate learning ability. Sleep spindles have also been observed to vary following learning in both young and older adults. We examined the effect of procedural task acquisition on sleep stages and on sleep spindles in an adolescent sample. Participants were 32 adolescents (17 female) between the ages of 12 and 19 years. Spindle activity was examined in three different frequency ranges: 11.00 – 13.50 Hz (slow), 13.51 – 16.00 Hz (fast), and 16.01 – 18.50 Hz (superfast). No changes in spindle density were observed after successful learning of the pursuit rotor task. This result was in contrast to a number of studies reporting spindle density increases following successful learning. In the present study, participants who successfully learned the task showed no changes in their sleep stage proportions, but participants who were not successful showed a decrease in the proportion of Stage 2 and increases in both SWS and REM sleep. We suggest that these changes in the sleep stages are consistent with the two stage model of sleep and memory proposed by Smith et al. (2004).